Antioxidant and antidiabetic properties of Garcinia cowa Roxb. extracts from leaves, fruit rind, and stem bark in different solvents - Wanna, Chanate; Boonman, Narumon; Phakpaknam, Sirirat (Plant Science Today, 2023)
The objective of this investigation was to assess the antioxidant and antidiabetic abilities of Garcinia cowa Roxb., a Thai native plant that has a history of use in traditional medicine in several countries. To achieve this goal, different plant parts, such as the leaves, fruit rind, and stem bark, were subjected to extraction with hexane, ethyl acetate, and 70% ethanol using the maceration method. The Folin-Ciocalteu technique was used to quantify the extracts' total phenolic content (TPC). The antioxidant assays, including DPPH, ABTS, and FRAP, and antidiabetic properties through the alpha-amylase and alpha-glucosidase inhibitory capacities of different extracts from G. cowa were assessed. The results revealed that the stem bark extracted with ethyl acetate displayed the highest level of TPC at 153.68 mg GAE/100 g DW. Compared to the other extracts, the stem bark ethyl acetate extract demonstrated the highest antioxidant activity in DPPH, ABTS, and FRAP assays with values of 436.86, 359.17, and 526.98 µmol TE/100 g DW, respectively. Further examination of the antidiabetic effects of stem bark extract in ethyl acetate exhibited the highest alpha-amylase and alpha-glucosidase inhibitory activities with IC50 values of 12.54, and 8.48 mg/mL, respectively. The findings of this research provide initial indications that G. cowa has both antioxidant and antidiabetic attributes and could be viewed as a potential therapeutic agent for managing diabetes.